Oriental Tower Mirrored in One of Treasure Island's Lagoons (H.S. Crocker Co., Inc.)
High above this Tower of the East at San Francisco's World's Fair, is a figure inspired by a Bangkok ceremonial umbrella. On wall leading to tower is a frieze representing the "Path of Darkness" by Lulu Hawkins Braghetta.